2017
DOI: 10.1007/s10943-017-0471-4
|View full text |Cite
|
Sign up to set email alerts
|

Are Religious Coping and Pain Perception Related Together? Assessment in Iranian Cancer Patients

Abstract: Pain of cancer had various significant side effects that based on the literature it can reduced by religious coping methods. This study aimed to investigate the relationship between religious coping and pain perception in Iranian cancer patients. In this cross-sectional study (October-December, 2015), 380 hospitalized cancer patients were entered to the study using accessible sampling. Data were collected by socio-demographic, Religious Coping and McGill pain questionnaires. Males (48.39 ± 13 ± 39; CI95: 46.41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…This is supported by other studies examining the effectiveness of religious coping for different individuals across various contexts. For instance, one study demonstrated that lower perceptions of pain among Muslim cancer patients in Iran were significantly related to positive religious coping (Goudarzian et al, 2018 ). This is in tandem with another study that found that religious coping increases the individual’s acceptance of unchangeable circumstances and tolerance towards perceived life hardships (Tehri-Kharameh et al, 2013 ).…”
Section: Coping Strategies and Religiositymentioning
confidence: 99%
“…This is supported by other studies examining the effectiveness of religious coping for different individuals across various contexts. For instance, one study demonstrated that lower perceptions of pain among Muslim cancer patients in Iran were significantly related to positive religious coping (Goudarzian et al, 2018 ). This is in tandem with another study that found that religious coping increases the individual’s acceptance of unchangeable circumstances and tolerance towards perceived life hardships (Tehri-Kharameh et al, 2013 ).…”
Section: Coping Strategies and Religiositymentioning
confidence: 99%
“…In the advanced stages of cancer, patients often need more self‐care information for various reasons, such as tumor growth and side effects from various treatments such as surgery, chemotherapy, and radiotherapy. 10 , 11 , 12 Increasing self‐care information in them will lead to increased participation in the treatment selection process, increase self‐care, reduce anxiety and worry, and thus improve quality of life. 13 , 14 , 15 , 16 Over the past few decades, extensive research efforts have been made to assess the information needs of patients with lung cancer, breast cancer, colorectal cancer, and various types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer can reduce people's ability to do routine work, followed by feelings of depression, frustration, and other psychological problems (4)(5)(6). Boyes et al (2012) also expressed that the highest level of support needs is in selfcare about physical needs and adaptation to illness in their own lives (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Moghaddam et al (2016), the most critical primary needs of patients with cancer were a de ciency in daily care, fatigue, pain, and the lack of advice from the treatment staff (8). Following this, self-care de ne as one of the most effective methods for controlling the physical and psychological effects (6). According to Orem's de nition, self-care can consider as covering all activities for the protection of life, health, and well-being (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation